(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2019)
The role of gesture in music has been widely investigated in different disciplines, from experimental psychology to aesthetics, from musicology to anthropology. What seems to drive the different researches is the question about the relationship arising between gestures and sound, and how this relationship affects the experience of music. In this article, I focus on the role of the hand in the production, listening and expression of music. After briefly referring to the influence of body development on language, I consider some typical responses to listening to music that involve the hand, suggesting that musical experience relies on the ability of the listener-performer to transform sound perceptions into motor units. In the conclusion, I delve deeper into the topic in a phenomenological direction, proposing that gestures can be configured as a bodily continuation of the musical material rather than mere motor reactions or conventional responses to sound perception.